Elucidating the multiple functions of POLDIP2 in Drosophila melanogaster. - Castaneda, Juan. (Tufts Archival Research Center, 2018)
We are interested in the potential role POLDIP2 might play regarding polymerase recruitment and switching during DNA repair in Drosophila melanogaster. Complete deletion of the gene was induced via the CRISPR Cas-9 editing system and a DsRed marker was inserted into the POLDIP2 locus via homology-directed repair. Intriguingly, flies homozygous for the deletion incur lethality at the second-instar larval stage. We are currently utilizing several approaches to determine the genetic basis for this lethality. Crosses between knockout mutants and a P-element stock suggest that POLDIP2 might be essential for viability. However, rescue of the homozygotes is impeded by the presence of a second site lethal mutations. Mutagen sensitivity assays will be conducted with these mutants to better characterize the interplay between POLDIP2 and the DNA repair and replication machineries.